2010
DOI: 10.1007/s10827-010-0237-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of the fractal dimension of the electroencephalogram during periodic breathing in heart failure patients

Abstract: The physiological mechanisms responsible for periodic breathing (PB) in heart failure (HF) patients are still debated. A role for rhythmic shifts in the level of wakefulness has been suggested, but their existence has never been proven. In this study we investigated the existence of an oscillation in EEG activity during PB in these patients and assessed its relationship with the ventilatory oscillation. EEG activity was measured by the fractal dimension (FD) and by a spectral technique (weighted mean frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In conclusion, in this study we have developed a hybrid method for continuous detection of state transitions, which integrates computer-based automatic analysis with visual microanalysis of major EEG ⁄ EOG features and events. We have tested our approach during Cheyne-Stokes respiration in patients with HF, a condition that is associated with repeated fluctuations in the level of wakefulness (Davies et al, 1999;Hanly et al, 1989;Maestri et al, 2010). The excellent agreement between the output of the statistical discriminator and the visual classification of unambiguous EEG activity supports the high reliability of the proposed method.…”
Section: Conclusi On Smentioning
confidence: 73%
See 2 more Smart Citations
“…In conclusion, in this study we have developed a hybrid method for continuous detection of state transitions, which integrates computer-based automatic analysis with visual microanalysis of major EEG ⁄ EOG features and events. We have tested our approach during Cheyne-Stokes respiration in patients with HF, a condition that is associated with repeated fluctuations in the level of wakefulness (Davies et al, 1999;Hanly et al, 1989;Maestri et al, 2010). The excellent agreement between the output of the statistical discriminator and the visual classification of unambiguous EEG activity supports the high reliability of the proposed method.…”
Section: Conclusi On Smentioning
confidence: 73%
“…, 2000). In a previous study we found that in the majority of patients the ventilatory oscillation is accompanied by rhythmic changes in EEG activity, suggestive of fluctuations between wakefulness and light NREM sleep (Maestri et al. , 2010).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Quantifying NREM vs. REM dominance may thus provide a pathophysiological phenotype. The oscillatory profile of respiratory oscillations or downstream respiration-driven or associated oscillations such as heart rate variability, blood pressure or even the electroencephalogram can be quantified (Maestri et al 2010). We present use of a ECG-derived cardiopulmonary coupling analysis to detect high loop gain apnea independent of conventional scoring.…”
Section: Introductionmentioning
confidence: 99%
“…In electronics, fractal conductance fluctuations in low-dimensional semiconductor devices [8][9][10], the chaotic nature of fractal conductance fluctuations in mesoscopic systems [11][12][13], and quantum-mechanical diffusion in semiconducting superlattices [14], were measured. In medical science, analyses of heart electroencephalograms for diagnostic purposes [15][16][17], or medical signals in general [18] are commonly used in clinical practice. Finally at a more global scale, in geoscience, fractal dimensions calculated for turbulence flow of atmospheric patterns are commonly used for weather prediction [19][20][21].…”
Section: Introductionmentioning
confidence: 99%